A figura do agente privado nas ações de improbidade administrativa - Giamundo, Camillo (2020)
The Brazilian Federal Constitution of 1988, in the search for the strengthening of its democratic precepts, regulated the penalties applicable to public agents responsible for acts of administrative improbity, and later attributed its effectiveness and regulation by Federal Law No. 8,429 of June 2nd, 1992. This law provides the extension and applicability to those who, even though not being public agents, induce or compete for the practice of the act of improbity, in direct or indirect way. Although the law expressly provides the possibility of its application to third parties unrelated to the Public Administration, the rules are not so clear and suffer from definitions and limitations, especially regarding the performance of private agents in cases of improbity. The present thesis intends to analyze the rules of the Brazilian Federal Constitution and the legislation pertinent to the accountability for acts of improbity and of application in matters outside the Public Administration, evaluating the peculiarities and problems faced, and the regulations of the Brazilian legal system